Parent and Teacher Perceptions of Elementary School Zoning System Policy - Izzatika, Amrina; Mustakim, Erni; Puspitasari, Eva Dwi; Hermawan, Jody Setya (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2022)
The number of students accepted at SD N 3 Kampung Baru decreased when new students were admitted. The research objective was to analyze and describe the responses of parents and teachers to the elementary school zoning system in Kampung Baru 3 Public Elementary School which focused on responses, opinions and assessments of the elementary school zoning system. The research method in this research is descriptive qualitative. Data collection techniques were carried out through in-depth interviews and documentation. Research shows that 1) the responses of parents and teachers to the zoning system policy are agreed/positive and some are disagree/negative, 2) the opinions of parents and teachers towards the zoning system policy reap positive and negative responses, 3) the assessment of parents and teachers towards the zoning system policy have an impact, both positive and negative.